Estudo da radiação ultravioleta e consequência nos agricultores da comunidade Guarumã no município do Acará-PA - AMARAL, Charleson Cruz (2021)
This paper seeks to study a study on ultraviolet radiation (UV) and effects on farmers belonging to the village of Guarumã in the municipality of Acará and from this study, seeks to address the importance of radiation prevention, avoiding possible injuries caused by excess. exposure to burns, spots on the body and skin cancer. Thus the study is developed taking into account the energy values for each wavelength range that make up the UVA, UVB and UVC radiation, the main problems that UV rays can provide, prevention against excessive incidence and from a field research with qualitative interviews with 7 farmers belonging to the community. .The issue of choosing the subject can be considered due to the fact that UV radiation is a danger to humans and that it is important to know the UV radiation in view of the consequences that may cause. The research concludes by showing that respondents are affected by UV radiation and that exposure has caused body damage, premature aging, burns and that while wearing light clothing to prevent direct exposure, they still suffer from exposure without the use of protective clothing. that could protect against harmful rays.